THE VIEW TO COLLISION OF NORMS OF THE CRIMINAL LAW - Jurkeviča, Tatjana; Šmits, Kaspars (Administrative and Criminal Justice, 2023)
Topicality and issue of a subject-matter Collision of norms in criminal law is incompleteness of legal provisions concerning collision of norms in Criminal law, despite the fact that such legal provisions have been developed in legal doctrine and recognized in case law. Goal of an article is to summarize and show these legal provisions in order to help readers and law enforcers to discern between multiplicity and aggregation of criminal offences, and collision of norms of the Criminal law.In essence – collision of norms of Special part of Criminal law differs from multiplicity (especially a conceptual aggregation) of criminal offences with a count of criminal offences and bodies of the crime (corpus delicti) corresponding to such offences. In a case of multiplicity two or more separate (unitary) criminal offences correspond to two or more bodies of the crime (corpus delicti) which are set out in Criminal law. Collision of norms of Special part of Criminal law occurs where two or more bodies of the crime (corpus delicti) corresponds to one, separate (unitary) criminal offence.In collision between general and special norm of a Special part of Criminal law, special norm (provision) must be applied.In collision between partial (narrower) and complete (broader) norm of Special part of Criminal law, broader norm (provision) must be applied. If such partial (narrower) norm sets out more severe punishment than a complete (broader) norm, both norms must be applied in accordance with rules of conceptual aggregation.In collision between aggravating and mitigating norms (provisions) mitigating norm must be applied, that is – a norm with a lesser punishment.In collision between mitigating norms (provisions), more mitigating norm must be applied.In collision between aggravating norms, more aggravating norm must be applied, that is – a norm wish sets out more severe punishment.Collision of norms (provisions) in administrative violations law is also decided in accordance the same rules of legal norm collision resolution, despite the fact that Latvian Administrative violations code does not contain relevant legal provisions.